2000
DOI: 10.1590/s1415-47572000000400045
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic behavior of economically important plant species: the relationship between fertility and male sterility

Abstract: Meiosis is an event of high evolutionary stability which culminates in a reduction of chromosome number. The normal and harmonious course of meiosis ensures gamete viability. The cytologic events of gametogenesis are controlled by a large number of genes that act from premeiotic to postmeiotic mitosis. Mutations in these genes cause anomalies that may impair fertility, and many abnormalities affecting plant fertility or causing total male sterility have been detected during the evaluation of meiotic behavior i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
2
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(124 citation statements)
references
References 42 publications
(40 reference statements)
6
109
2
7
Order By: Relevance
“…According to Pagliarini (2000), the most common meiotic abnormalities observed in several species is the irregular chromosome segregation, characterized by early migration or laggard chromosomes at metaphase I and anaphase I. Considering that the meiotic behavior of a plant is directly related to their degree of fertility, the changes observed during cell division may be reflected in the viability of pollen grains (Defani-Scoarize et al 1996).…”
Section: Resultsmentioning
confidence: 99%
“…According to Pagliarini (2000), the most common meiotic abnormalities observed in several species is the irregular chromosome segregation, characterized by early migration or laggard chromosomes at metaphase I and anaphase I. Considering that the meiotic behavior of a plant is directly related to their degree of fertility, the changes observed during cell division may be reflected in the viability of pollen grains (Defani-Scoarize et al 1996).…”
Section: Resultsmentioning
confidence: 99%
“…The stickiness is characterized as a chromosome grouping during some phases of the cellular cycle that according to PAGLIARINI (2000), may be caused by environmental causes as well as genetic control. GAULDEN (1987) suggest that chromosome stickiness its caused by a failure in the functioning of one of the two non-histone proteins involved in the process of chromosome separation and segregation.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that the PMCs with unequal distribution of chromosomes due to the presence of laggards, however, did not exceed 10-15% of the total PMCs analyzed at AI. Unpaired chromosomes (univalents) in diploid taxa are reported to be the main factor resulting in the abnormal distribution of chromosomes at anaphase I and/or II (Singh 1993, Rao 1990, Pagliarini 2000, Kumar and Rao 2003. Gill et al (1979) and Gill and Singhal (1988a, b) have reported that the occurrence of accessory chromosomes (B) is a regular feature of many woody tree species.…”
Section: Discussionmentioning
confidence: 99%